Characterisation of atypical Aeromonas salmonicida isolates from Cleaner Fish in the United Kingdom - Buba, Elizabeth (University of Stirling, 2021)
Cleaner fish such as ballan wrasse (Labrus bergylta) and lumpfish (Cyclopterus lumpus) are currently used as a biological approach to controlling sea lice (Lepeophtheirus salmonis) in Atlantic salmon (Salmo salar) in the United Kingdom and elsewhere. However, these newly domesticated fish species are susceptible to infection by various bacterial pathogens, including atypical strains of A. salmonicida (aAs) that causes atypical furunculosis. Little is known of the diversity of aAs strains causing problems and no commercially licensed vaccine is presently available. Instead, multivalent autogenous vaccines (which include aAs strains) are used to control disease incidences, though outbreaks do still occur and these must be treated with antibiotics. For vaccines to be effective, the formulation must include isolates that confer protection against the prevalent circulating strains. Monitoring of the susceptibility of isolates to antibiotics is critical for these drugs to remain efficacious. Therefore, the aim of this thesis was to investigate the diversity of aAs strains causing disease problems in the UK and determine their antibiotic susceptibility. Seventy-seven aAs isolates collected from six different cleaner fish sites in the UK were characterised by phenotypic and genotypic methods. Two strain lineages were identified within the UK isolates by pulsed-field gel electrophoresis (PFGE), with a predominant group composed of ballan wrasse isolates and a minor cluster of mainly lumpsucker isolates. One pulsotype (B2) was detected at five UK sites and this accounted for 73% of isolates. The existence of two genetic groups was further supported by whole-genome sequencing (WGS) and virulence array protein gene typing of the A-layer (vapA). PFGE group B correlated with vapA type V isolates from ballan wrasse and PFGE group A with genotype vapA type VI typically from lumpsuckers. Additionally, the substrate, B-methyl-D-Glucoside from biolog assay differentiated between vapA type V and VI of aAs. Immuno-proteomic ...